A multiple suture craniosynostosis with fusion of sagittal, metopic, and bilateral coronal sutures: Case report - Başkurt, Ozan; Çine, Hidayet Ş.; Uysal, Ece; Hicdonmez, Tufan (Ukrainian Neurosurgical Journal, 2024)
Multisutural synostosis, characterized by the fusion of multiple cranial sutures without a clear underlying syndrome, represents a rare subtype of craniosynostosis. Particularly uncommon is the simultaneous fusion of the sagittal, metopic, and bilateral coronal sutures. This report details the case of a 50-month-old boy, who had an abnormal head shape due to the simultaneous fusion of four sutures. The closure of the sagittal, metopic, and bilateral coronal sutures has led to a distinct head shape marked by flattening of the forehead and anterior skull, contrasting with the typical Mercedes-Benz pattern observed in craniosynostosis cases. Surgical intervention involved osteotomy with symmetrical barrel staves in the parietal and frontal regions, resulting in improved forehead contour.